Effects of the SARS-CoV2-Lockdown on Pediatric Care in the Rhine-Main Area - Donath, Helena; Zielen, Stefan; Wittekindt, Boris; Klingebiel, Thomas; Graf, Jürgen; Eckrich, Martin; Walter, Christian; Blümchen, Katharina (Klinische Pädiatrie, 2020)
Background The effects of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and lockdown on pediatric diseases and care are not well characterized in Germany.Patients and Methods To investigate the effects of the lockdown on pediatric medical care in the Rhine-Main area, a survey asking 115 pediatricians and an analysis of the inpatient admissions at the Department for Children and Adolescents Goethe-University, Frankfurt in April 2020 compared to April 2019 was performed.Results 65/115 (56.5%) pediatricians answered the survey. Pediatricians estimated the reduction of patient consultations in April 2020 vs. 2019 by 40% (median), however, according to their practice administration software, patient visits decreased by 30%. The median number of cases with the diagnosis J21 (acute bronchitis) were significantly less in April 2020 vs. April 2019 (50 vs. 10 cases per pediatrician; p<0.001). Simultaneously, hospital admissions decreased by 43.7% from 402 total cases in April 2019 to 226 cases in April 2020. Hospital admissions due to acute respiratory tract infections or asthma exacerbations as well as neonatal and oncological disorders were significantly reduced compared to the previous year (83.7; 38.1 and 22.1% respectively less to 2019).Conclusion The lockdown in April 2020 resulted in significantly fewer visits to pediatricians in general practice and hospital admissions, especially for acute respiratory tract infections. The health and economic consequences are discussed.
Keywords: Lockdown; acute respiratory tract infection; pediatric care; COVID-19; pandemic; social distancing